If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4.5=7x-1/6
We move all terms to the left:
4.5-(7x-1/6)=0
We add all the numbers together, and all the variables
-(+7x-1/6)+4.5=0
We get rid of parentheses
-7x+4.5+1/6=0
We multiply all the terms by the denominator
-7x*6+1+(4.5)*6=0
We add all the numbers together, and all the variables
-7x*6+28=0
Wy multiply elements
-42x+28=0
We move all terms containing x to the left, all other terms to the right
-42x=-28
x=-28/-42
x=2/3
| 15(h+3)=45 | | 6y-10=2y-7 | | h+2=-8 | | 0=-0.005x^2+0.7x+3.5 | | 13(x+2)=-15 | | -3x-13=11 | | 2x+0,8x=500 | | 2(5+3x) = 2(5) +2(3x) | | 5/6=(4x/12)+(3x/12) | | 3w+w^2+1=10-w | | x/3=(5/6)-(x/4) | | -k+4(k+1=2k | | 7x–12=2x+28 | | 5(3×-2)=5(4x+1) | | 2.5s=15 | | (3x-4x)/12=-10/12 | | (4/5)/x+x=252 | | 6x-3=9x+11 | | 3x+(5x-8)=180 | | 118098=2(3)^x-1 | | 4/5x+x=252 | | -10(b+6)=88 | | X/4=15/x=24/16 | | 9x-28=90 | | 3x^2-2x+10=x^2+2(x+5) | | 46-3t=-2346 | | 3(2x+1)=17-2(×-1) | | 2(x+3)+9=5+x-1 | | U(2)-23u+22=0 | | 9y-8=76 | | 3/u=24 | | 46+3t=23 |